Complications of arterial hypertension - Usmonov Jamshidbek Rustamjon oʻgʻli (Journal of Medical Genetics and Clinical Biology, 2024)
Complications of arterial hypertension (AH), beginning to show a direct relationship with the level of blood pressure 145/95 mm Hg. Art., for many decades are the leading cause of death among all causes of death. Arterial hypertension, without a doubt, is the leading medical and social problem of our time, the role of which in mortality and disability of people continues to grow, despite the great attention paid to this problem by the scientific community, practitioners and authorities. Against the backdrop of growing knowledge and progress in the field of pharmacology and therapy of hypertension, the frequency of achieving target blood pressure today in the United States and European countries has stabilized by 25-34%, in Russia in the 1990s. was - in men 5.7%, in women - 17.5%, decreasing with age[2]. According to the National Guidelines for the Prevention, Diagnosis and Treatment of Arterial Hypertension (draft) in Russia in 2006, this indicator slightly improved (21.5%)[2, 4]. Apparently, it is within these limits that one can speak of the limit of population possibilities of the unconditionally dominant drug therapy of hypertensive conditions today.